Forecasting recorded property crime using a time-series econometric model - Deadman, Derek F. (The British journal of criminology, 1997)
This paper uses a time-series econometric model, previously published by Pyle and Deadman (1994), in order to forecast levels of recorded property crime for the years 1992-96 inclusive. The model forecasts well for the period 1992-95 inclusive, in that it picks up the turning points in the series for recorded theft (in 1992) and recorded burglary (in 1993) and predicts the continuing increase in recorded offences of robbery. The model forecasts a further fall in the level of recorded theft in 1996, if GDP grows at the rate of 2.1 per cent predicted by the NIESR for that year. However, the model predicts that the fall in the number of recorded offences of burglary may come to an end in 1996 and that offences of burglary may even increase slightly. The number of recorded offences of robbery is predicted to continue to increase. A method of separating the effects upon recorded crime of economic changes from criminal justice changes is suggested